Myoplasty as a method for the prevention of prolonged lymphorrhea after radical mastectomy - A. Kh. Ismagilov; A. S. Vanesyan; G. I. Shakirova; A. R. Muzafarov (ABV-press, 2015)
Lymphorrhea plays a leading role in the development of post-mastectomy pain syndrome and gives rise to lymphocele, local complications, and delayed adjuvant therapy and it is accompanied by longer hospitalization and a larger number of outpatient visits.Objective: to evaluate the efficiency of armpit myoplasty in the prevention of lymphorrhea after radical mastectomy. The Department of Mammology, Republican Clinical Oncology Dispensary, Ministry of Health of the Republic of Tatarstan, has developed a procedure to prevent prolonged lymphorrhea via armpit myoplasty using the distal end of the minor pectoral muscle (Patent No. 2385673 dated April 10, 2010), which minimizes the risk of seroma formation in the armpit. The investigation is based on the analysis of the results of radical surgery in 545 patients. All the patients were divided into a study group (n = 256) that had undergone armpit myoplasty and classical Patey's mastectomy and a control group (n = 289) that had Patey's mastectomy only. The investigation has revealed that armpit myoplasty using the minor pectoral muscle is an effective technique to prevent seromas in the postmastectomy wound area; in this case, there is a decrease in the volume and duration of lymphorrhea and in the length of hospital stay.